RADIOPROTECTION QUALITY OF A NEW ORAL REMEDY “APIOR” UNDER CONDITIONS OF RADIATION STOMATITIS IN RATS - L.S. Kravchenko; S.A. Schnaider; Ya.F. Burdina (Український стоматологічний альманах)
Radiation stomatitis development is the basic problem in management of anti-cancer therapy in patients who had X-ray therapy associated with cancer at the region of head and neck. Prophylaxis and medical treatment of radiation defeats are not always effective.